Mathematical Modelling of Targeted Delivery of Medicines to a Respiratory Tract - Antonov D. V. Dmitry Vladimirovich; Sazhin S. S. Sergey Stepanovich; Strizhak P. A. Pavel Alexandrovich; Nagatkina O. V. Olga Vladimirovna (2025, 2025)
Title screen